Analisis Kualitas Pelayanan Lembaga Amil Zakat terhadap Loyalitas Muzaki - Permatasari, Cindy; Huda, Nurul (Ikatan Da'i Indonesia, 2022)
The research aims to know the influence of the service quality management institution of zakah directly against muzaki loyalty; as well as the role of the interaction of the service quality management institution of zakah and satisfaction muzaki as moderating variable in influencing loyalty muzaki, through the dissemination of a questionnaire of 150 muzaki in Jabodetabek area in November 2013, with Structural Equation Model analysis method (SEM) program LISREL 8.5. The results showed there was a positive influence of variable quality of service directly to the variable muzaki loyalty but not significant; as well as the quality of service has a role which is not too great with support in influencing loyalty muzaki satisfaction muzaki. So the role of the interaction of the service quality and customer satisfaction as a moderating variable muzaki in influencing loyalty muzaki is small enough.